Analisis faktor-faktor yang mempengaruhi pendapatan petani jagung manis di Kampung Semangga Jaya, Distrik Semangga - Sahra, Jihan Fatimatus; Untari, Untari; Nurliah, Nurliah (Universitas Musamus, Merauke, Papua, 2024)
Indonesia's corn production has not fully met the community's consumption needs because it is vulnerable to climate and seasonal changes, which affect farmers' income and welfare. The study aims to analyze the factors that influence the income of sweet corn farmers in Semangga Jaya Village, Semangga District simultaneously and partially and the variables that have a dominant influence on the income of sweet corn farmers. The study was carried out in Semangga Jaya Village from May to July 2024. The study used a quantitative descriptive approach. The data analysis method used was multiple linear regression analysis with 4 variables measured, namely selling price (X1), demand (X2), climate (X3) and supply (X4) on the dependent variable of sweet corn farmers' income (Y). The results showed that the four variables simultaneously had a significant effect on the income of sweet corn farmers by 81.9%. Partially, the income of sweet corn farmers is seen based on the influence of the selling price factor of 15.7%, demand has an effect of 2.9%, climate has an effect of 32.8% and supply has an effect of 23.4%. The results of the study concluded that climate factors are more dominant in influencing the income of sweet corn farmers in Semangga Jaya Village.